(untitled) (Revista Contexto & Saúde, 2026)
Objective: This study aimed to evaluate microbiological quality of multipurpose water at Maranhão Multimodal Terminal and to determine occurrence of enterobacteria as support for hygienic-sanitary control in production processes. Method: Individual water samples were collected from 23 food stalls and three drinking fountain taps available for users, totaling 27 samples. An enzymatic chromogenic method was applied to quantify most probable number (MPN) of total coliforms and Escherichia coli. Enterobacteria were identified through bacterial isolation followed by morphotintorial and biochemical characterization of isolates. Results: All samples analyzed showed absence of E. coli, whereas 59.25% was positive for total coliforms, with counts ranging from 1.0 to >2,419.6 MPN/100 mL. Thirty bacterial strains were isolated from coliform-positive samples. These isolates comprised genus Enterobacter sp. and species Shimwellia blattae, Citrobacter koseri, Klebsiella pneumoniae subsp. pneumoniae, Serratia fonticola, Enterobacter cloacae, Proteus myxofaciens, and Proteus mirabilis. Conclusion: Although multipurpose water samples did not contain E. coli, they may function as reservoirs of ubiquitous enterobacteria with clinical relevance (E. cloacae, K. pneumoniae, and P. mirabilis), indicating potential risk to users and need for adequate water treatment. The findings presented here may support effective surveillance and control actions aimed at ensuring microbiological safety of water intended for human consumption at Maranhão Multimodal Terminal.